The Laguna copperplate inscription tenth-century Luzon, Java, and the Malay world - Clave, Elsa (Philippine Studies: Historical and Ethnographic Viewpoints, 2022)
The Laguna Copperplate Inscription is one of very few Philippine historical documents dating from the precolonial period and the only one bearing information on the social life of the Manila region before the arrival of the Spanish. Building on previous studies which discussed the significance of the inscription in the context of Luzon and the Philippines, this article proposes a reading of the inscription in the larger context of maritime Southeast Asia. We focus on how this document complicates the current understanding of the historical roles of the Malay language. On this basis, we call for a revision of the notion of a "Malay World."